Protease-inhibiting, molecular modeling and antimicrobial activities of extracts and constituents from Helichrysum foetidum and Helichrysum mechowianum (compositae) - Malolo, Fanny-Aimee Essombe; Nouga, Achille Bissoue; Kakam, Antoine; Franke, Katrin; Ngah, Lidwine; Flausino, Otavio [UNESP]; Mpondo, Emmanuel Mpondo; Ntie-Kang, Fidele; Ndom, Jean Claude; Bolzani, Vanderlan da Silva [UNESP]; Wessjohann, Ludger (Biomed Central Ltd, 2015)
Background Helichrysum species are used extensively for stress-related ailments and as dressings for wounds normally encountered in circumcision rites, bruises, cuts and sores. It has been reported that Helichysum species are used to relief abdominal pain, heart burn, cough, cold, wounds, female sterility, menstrual pain. Results From the extracts of Helichrysum foetidum (L.) Moench, six known compounds were isolated and identified. They were 7, 4′-dihydroxy-5-methoxy-flavanone (1), 6′-methoxy-2′,4, 4′-trihydroxychalcone (2), 6′-methoxy-2′,4-dihydroxychalcone -4′-O-β-D-glucoside (3), apigenin (4), apigenin-7-O-β-D-glucoside (5), kaur-16-en-18-oic acid (6) while two known compounds 3,5,7-trihydroxy-8-methoxyflavone (12), 4,5-dicaffeoyl quinic acid (13) together with a mixture of phytosterol were isolated from the methanol extract of Helichrysum mechowianum Klatt. All the compounds were characterized by spectroscopic and mass spectrometric methods, and by comparison with literature data. Both extracts and all the isolates were screened for the protease inhibition, antibacterial and antifungal activities. In addition, the phytochemical profiles of both species were investigated by ESI-MS experiments. Conclusions These results showed that the protease inhibition assay of H. foetidum could be mainly attributed to the constituents of flavonoids glycosides (3, 5) while the compound (13) from H. mechowianum contributes to the stomach protecting effects. In addition, among the antibacterial and antifungal activities of all the isolates, compound (6) was found to possess a potent inhibitor effect against the tested microorganisms. The heterogeneity of the genus is also reflected in its phytochemical diversity. The differential bioactivities and determined constituents support the traditional use of the species. Molecular modelling was carried out by computing selected descriptors related to drug absorption, distribution, metabolism, excretion and toxicity (ADMET).
Keywords: Compositae; Helichrysum foetidum; Helichysum mechowianum; ESI-MS; Protease inhibition assay; Antimicrobial